Governance and Public Administration (Botswana) - World Bank (World Bank, Washington, DC, 2012)
In 1993, the Government of Botswana launched a productivity movement to improve civil service performance. The centerpiece of the movement was the introduction of Work Improvement Teams (WITs). A WIT is a group of civil servants from the same work unit, irrespective of divisional status, who meet regularly to solve problems, examine improvement opportunities and develop problem solving skills. It is inspired by the model in Singapore which in turn is an adaptation of the Japanese Quality Control Circle. WITs are well established in Singapore as a mechanism for improving the performance of the work force in the public sector and have been credited with the successful implementation of 22,000 improvements in public organizations. A twinning arrangement between the Botswana Institute of Administration and Commerce (BIAC) and Singapore's Civil Service Training Institute was adopted as the instrument for transplanting WITs into Botswana. WITs can be potentially effective tools for productivity improvement by helping to establish a mind-set that seeks: optimum performance, participative leadership and team work, innovative work styles, strong client orientation and empowerment of people. However, it will take an estimated 5-10 years to witness a significant impact on productivity, with employees themselves, rather than their management, seeking to actively improve efficiency and the quality of work-life.